Under-five mortality rate (U5MR) in Haiti from 1994 to 2016: Trends and factors of variation. (June 2022) - Ouedraogo, Adama; Jean Simon, David; Kiragu, Ann
Highlights: In Haiti, the under-five mortality rate (U5MR) decreased from 131‰ in 1994 to 86‰ in 2005, but it has stopped declining since 2005; The U5MR has been growing in the "Ouest" department, the most populous, since 2005. The many successive and repeated political crises and the devastating earthquake of 2010 that the country has experienced seems to be the causes of this situation. Abstract: Background: Since 2000, countries have made substantial progress in reducing under-five mortality, but Haiti, an impoverished country in the Latin America and Caribbean region, faces major health challenges, including a high level of child mortality. However, few studies have focused on analysing trends in the under-five mortality rate (U5MR), determinants and geographical disparities within the country. Objectives: This study analyses the trend of U5MR in Haiti between 1994 and 2016, at national and departmental levels, and also examines differentials in the U5MR according to medical, demographic, and socio-economic characteristics of the population, and their evolution over time. Methods: The study used data from Haiti's Demographic and Health Surveys (DHS) conducted between 1994 and 2016. The U5MR for Haiti was estimated based on the DHS Measure method, and a Cox proportional hazard model was used to determine factors contributing to under-five mortality. Results: The U5MR decreased from 131‰ (95% CI 120–142) in 1994 to 81‰ (95% CI 73–89) in 2016. The decline was very sharp between 1994 and 2005, but during the 2005–2016 period, the U5MR remained unchanged. At the departmental level, mortality declined in most of the nine departments, but a clear upward trend was observed in the "Ouest" department. Multivariate analysis revealed that insufficient antenatal care, a lack of breastfeeding, twin births, children of young mothers, high birth order, and poor households were significantly associated with higher mortality risks in Haiti. Conclusions: Achieving child survival in Haiti will require resources and policy to accelerate the decline of the current rates in most departments and prevent the significant rise in the "Ouest" department.